Planned or emergent? An evaluation of a Master’s in Health Professions Education programme - Elize Archer; Susan Camille van Schalkwyk; Mariette Volschenk; Anna Maria Susanna Schmutz (BMC Medical Education, 2022)
Abstract Background Programme developers have the responsibility of ongoing programme renewal and evaluation to ensure that curricula remain responsive to rapidly changing educational and healthcare contexts. In reporting on programmes, significant emphasis is often placed on content and outcomes of Master’s in Health Professions Education (MHPE) programmes. However, less emphasis has been placed on meaningful evaluation of all aspects of these programmes, particularly from a student perspective including what worked and what needs to be enhanced, as well as any emergent or unplanned factors. As the number of established MHPE programmes increases, so does the need for evaluation models that consider programme complexity. In this article we consider a MHPE programme against a model that provided scope for going beyond ‘did it work?’ Our intention was to determine whether the renewed MPhil in HPE programme was implemented as planned, and to which extent it achieved the planned outcomes. Methods This programme evaluation was conducted in an interpretive paradigm. We collected qualitative data at two points. Firstly, at the start of students’ first-year with voluntary participation in focus groups and secondly, a year later with voluntary participation in individual interviews. Two members of the research team performed the initial thematic analysis of both the focus group interviews and the individual interviews. Thereafter, the full author team worked collaboratively discussing the themes until we reached consensus, looking specifically to identify any “emergent” factors. Results We identified three themes in the student data related to the process of implementing the new programme and the outcomes from it, including those aspects that could be regarded as emergent or unplanned: balancing work, personal lives and studies; managing the hybrid learning approach; and the scholarly journey. Conclusions While many of the outcomes of the renewed programme were met, not all manifested as had been planned. The experience of the programme differed from one student to the next such that at the end of the two years they were at different points in their scholarly journeys. We realised that although we sought to be pedagogically sound in the process of curriculum renewal, we did not take into account the complex matrix of influences that sit outside the formal curriculum. Future renewal activities should intentionally and sensitively consider those factors, both planned and emergent, that influence a student’s journey towards becoming a scholarly teacher and teaching scholar.